Modern potential of preparation of intestine to endoscopy in pediatric practice - S. I. Erdes; N. M. Leonevskaya; M. M. Lokhmatov; M. A. Ratnikova; T. N. Budkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy and safety of sodium phosphate solution (Fleet® phospho-soda) as an agent for preparation of intestine to endoscopic investigation.Material and methods. Overall 28 teenagers aged 13–17 years were enrolled to original study (mean age 14,96±1,05 year). Study inclusion criterion was the necessity of preparation of intestine before endoscopy. Exclusion criteria were: incomplete/complete ileus, megacolon (congenital/acquired), acute inflammatory diseases and disorder of large intestine integrity, renal/ heart failure. Estimated parameters included: general state of the patient, dynamics of clinical manifestations, quality of preparation of intestine (visualization capability, presence of fecal masses), time of bowel movement (development of stool), changes of hemodynamic scores.Results. In 89,3% of children good visualization of intestine has been achieved. Tolerability of agent was regarded as good in 46,4%, in 53,6% of patients – as satisfactory. Side effects (nausea, dizziness, flatulence etc.) were short-term and transient. Hemodynamic parameters did not undergo statistically significant changes.Conclusion. Solution of sodium phosphate (FLEET® phospho-soda) is an efficient agent for preparation of intestine for endoscopic investigations as it provides good visualization of mucosa and has few side effects. Its application in pediatric practice provides the best compliance, as compared to other modes, because it does not require intake of high volume of fluid.